Milk and Its Sugar-Lactose: A Picture of Evaluation Methodologies - Loretta Gambelli (Beverages, 2017)
Lactose is the major disaccharide found in milk, and is catabolized into glucose and galactose by the enzyme lactase. Lactose is an important energy source and ssometimes it is referred to simply as milk sugar, as it is present in high percentages in dairy products. Lactose is the primary source of carbohydrates during mammal development, and represents 40% of the energy consumed during the nursing period. Lactose-intolerance individuals have a lactase deficiency; therefore, lactose is not completely catabolized. Lactose intolerance is a significant factor in the choice of diet for many sick people, therefore its content in foods must be monitored to avoid disorders and illnesses. This has created the need to develop simple methods, such as polarimetry, gravimetric, middle infrared, differential pH and enzymatic monitoring, but all these methods are time-consuming, because they required extensive sample preparation and cannot differentiate individual sugars. In order to quantify low levels of lactose, new and more accurate analytical methods have been developed. Generally, they require equipment such as HPLC or High Performance Anion Exchange with Pulsed Amperometric Detection (HPAE-PAD).